2002
DOI: 10.1097/00007691-200208000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Trough, 2-Hour, and Limited AUC Blood Sampling for Monitoring Cyclosporin (Neoral®) at Day 7 Post–Renal Transplantation and Incidence of Rejection in the First Month

Abstract: The use of alternative strategies to the traditional pre-dose/trough (C0) blood sampling for cyclosporine (CsA) therapeutic drug monitoring has the potential to revolutionize analytical practices which have, in many centers, been established for some 20 years. While the C0 sample has previously been recommended, current attitudes are increasingly proposing alternatives for assessing CsA exposure, including various limited sampling strategies of the AUC (lssAUC) in the early postdose period, or alternative sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
1
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(45 citation statements)
references
References 46 publications
0
42
1
2
Order By: Relevance
“…This was illustrated by data showing that the rates of acute rejection and nephrotoxicity in patients with trough CsA concentrations within a defined therapeutic range remained 59 and 63%, respectively. 42 Subsequent work showed that trough CsA levels did not correlate with drug exposure as estimated by the area under the concentration time curve (AUC) 43 and others demonstrated that the correlation between trough levels and clinical outcomes was relatively poor 42,[44][45][46][47][48][49][50] in the settings of renal, liver and heart transplantation.…”
Section: Cyclosporin Monitoring In the Setting Of Solid Organ Transplmentioning
confidence: 99%
“…This was illustrated by data showing that the rates of acute rejection and nephrotoxicity in patients with trough CsA concentrations within a defined therapeutic range remained 59 and 63%, respectively. 42 Subsequent work showed that trough CsA levels did not correlate with drug exposure as estimated by the area under the concentration time curve (AUC) 43 and others demonstrated that the correlation between trough levels and clinical outcomes was relatively poor 42,[44][45][46][47][48][49][50] in the settings of renal, liver and heart transplantation.…”
Section: Cyclosporin Monitoring In the Setting Of Solid Organ Transplmentioning
confidence: 99%
“…[5][6][7] In solid organ transplantation, the use of C0 monitoring has been associated with a high incidence of renal dysfunction. 8 In these patients, levels taken 2 h after a dose (C2) appear to correlate best with C max and area under the concentration-time curve 0-4 h (AUC 0À4h ), 9 and monitoring and dose adjustments based on C2 levels has been associated generally with improved renal function without an increased risk of graft rejection after heart, 10 liver 11 and renal transplantation, 12 although not all studies have demonstrated benefit with this approach. 13,14 Alterations in GI motility and mucosal integrity by conditioning regimens or GVHD mean that observations in solid organ transplantation may not apply to recipients of allo-SCT.…”
Section: Introductionmentioning
confidence: 99%
“…3 Thus, concentration sampling 2 h after dose intake (C2) has been suggested as a better measure of both total drug exposure and effect in kidney, heart and liver transplant patients. [4][5][6][7] In other series of liver and heart transplant patients, no clinical superiority (lower incidence of acute graft rejections) was demonstrated using C2 levels. 8,9 A definite drawback of C2 measures is that they are sensitive to minor deviations in sampling time.…”
Section: Introductionmentioning
confidence: 94%